Analisis Aspek Keuangan: Studi pada Bank BJB - Rozikin, Mochammad Ainur (Maliki Interdisciplinary Journal, 2025)
This article examines the business feasibility study of Bank BJB with an emphasis on financial aspects. The research aims to assess the financial performance of Bank BJB and its viability in conducting operations and achieving business objectives. The data used is sourced from Bank BJB's published financial statements and other relevant secondary sources. The analysis methods include financial ratio analysis, trend analysis, and financial projections. The results indicate that Bank BJB has a healthy and stable financial performance, as evidenced by good financial ratios and positive growth trends. However, certain aspects such as the management of non-performing loans and operational efficiency require attention. Overall, Bank BJB is deemed financially viable to continue its operations and expand its business.